Modifying adolescent interpretation biases through cognitive training: effects on negative affect and stress appraisals. - Telman, MD; Holmes, E; Lau, J (2013)
Adolescent anxiety is common, impairing and costly. Given the scale of adolescent anxiety and its impact, fresh innovations for therapy are in demand. Cognitive Bias Modification of Interpretations (CBM-I) studies of adults show that by training individuals to endorse benign interpretations of ambiguous situations can improve anxious mood-states particularly in response towards stress. While, these investigations have been partially extended to adolescents with success, inconsistent training effects on anxious mood-states have been found. The present study investigated whether positive versus negative CBM-I training influenced appraisals of stress, in forty-nine adolescents, aged 15-18. Data supported the plasticity of interpretational styles, with positively-trained adolescents selecting more benign resolutions of new ambiguous situations, than negatively-trained adolescents. Positively-trained adolescents also rated recent stressors as having less impact on their lives than negatively-trained adolescents. Thus, while negative styles may increase negative responses towards stress, positive styles may boost resilience.